2016
DOI: 10.1016/j.ridd.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary skills are well developed in university students with dyslexia: Evidence from multiple case studies

Abstract: Most studies in adults with developmental dyslexia have focused on identifying the deficits responsible for their persistent reading difficulties, but little is known on how these readers manage the intensive exposure to written language required to obtain a university degree. The main objective of this study was to identify certain skills, and specifically vocabulary skills, that French university students with dyslexia have developed and that may contribute to their literacy skills. We tested 20 university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 64 publications
3
71
0
2
Order By: Relevance
“…Other studies have similarly found that children with RD can rely on morphological structure to decode words faster, despite decoding difficulties [38,39]. Vocabulary skills have also been implicated as a compensatory mechanism for college students with RD [40], and have been shown to mediate between impaired verbal working memory and oral reading fluency in adolescents with RD [41]. More superior verbal reasoning skills in general have been shown to explain higher reading, spelling, morphological, and syntactic skills in students with RD [42].…”
Section: Cognitive Resiliencementioning
confidence: 99%
“…Other studies have similarly found that children with RD can rely on morphological structure to decode words faster, despite decoding difficulties [38,39]. Vocabulary skills have also been implicated as a compensatory mechanism for college students with RD [40], and have been shown to mediate between impaired verbal working memory and oral reading fluency in adolescents with RD [41]. More superior verbal reasoning skills in general have been shown to explain higher reading, spelling, morphological, and syntactic skills in students with RD [42].…”
Section: Cognitive Resiliencementioning
confidence: 99%
“…Secondly, since the semantic knowledge associated with words seems to be preserved both in children (Vellutino et al, 1995) and adults (Cavalli et al, 2016;Elbro et al, 1994) with dyslexia, and since neuroimaging studies show no differences between the spatial distribution of the brain areas involved in semantic processing by dyslexic and skilled readers (Helenius, Salmelin, Service, & Connolly, 1999;Rüsseler, Becker, Johannes, & Münte, 2007), we assume that dyslexics are likely to capitalize on the semantic dimension of morphology to develop morphological knowledge. In accordance with this hypothesis, a recent study conducted in Dutch showed that in the context of a productive dictation task, university students with dyslexia made slightly fewer grammatical errors and proportionally more phonological and orthographic errors than their control peers in spelling words and sentences to dictation.…”
mentioning
confidence: 99%
“…In contrast, dyslexic adults performed well in the semantic fluency task (Hatcher et al, 2002) and vocabulary tasks (e.g., Cavalli et al, 2016) but the success of children were mixed (Joanisse et al, 2000; White et al, 2006; Everatt et al, 2008; Landerl et al, 2009; Varvara et al, 2014). …”
Section: Dissociating Functional Illiteracy From Illiteracy and Dyslexiamentioning
confidence: 97%